Biochemical Characterization and Polyester-Binding/Degrading Capability of Two Cutinases from Aspergillus fumigatus - Haizhen Wang; Tianrui Zhang; Kaixiang Chen; Liangkun Long; Shaojun Ding (Microorganisms)
Two recombinant cutinases, AfCutA and AfCutB, derived from Aspergillus fumigatus, were heterologously expressed in Pichia pastoris and systematically characterized for their biochemical properties and polyester-degrading capabilities. AfCutA demonstrated superior catalytic performance compared with AfCutB, displaying higher optimal pH (8.0–9.0 vs. 7.0–8.0), higher optimal temperature (60 °C vs. 50 °C), and greater thermostability. AfCutA exhibited increased hydrolytic activity toward p-nitrophenyl esters (C4–C16) and synthetic polyesters. Additionally, AfCutA released approximately 3.2-fold more acetic acid from polyvinyl acetate (PVAc) hydrolysis than AfCutB. Quartz crystal microbalance with dissipation monitoring (QCM-D) revealed rapid adsorption of both enzymes onto polyester films. However, their adsorption capacity on poly (ε-caprolactone) (PCL) films was significantly higher than on polybutylene succinate (PBS) films, and was influenced by pH. Comparative modeling of catalytic domains identified distinct structural differences between the two cutinases. AfCutA possesses a shallower substrate-binding cleft, fewer acidic residues, and more extensive hydrophobic regions around the active site, potentially explaining its enhanced interfacial activation and catalytic efficiency toward synthetic polyester substrates. The notably superior performance of AfCutA suggests its potential as a biocatalyst in industrial applications, particularly in polyester waste bioremediation and sustainable polymer processing.